Learning About e-Learning – The eUniversity Experience - Wilson, Casey McQuinn (Proceedings of the International Conference on Networked Learning, 2004)
This paper presents the experiences to date of an ‘e-learning’ development project which aimed to successfully develop, deliver and support ‘e-materials’ for a masters level degree course in Information Technology and Management 100% online to a world wide community. The e-learning development project was established in early 2002 and is now at the stage that the majority of the e-materials have been developed and delivery of the MSc course is underway. This paper critically evaluates the e-learning development experience to date. Upon reflection and analysis of the development process preliminary lessons have been drawn and are discussed here. Through this discussion comment can be made about developing e-learning materials in Higher Education.